2022
DOI: 10.3389/fgene.2022.984996
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: The third-generation sequencing confirmed a novel 7.2 Kb deletion at β-globin gene in a patient with rare β-thalassemia

Abstract: Background: Thalassemia was the most common monogenic diseases worldwide, which was caused by mutations, deletions or duplications in human globin genes which disturbed the synthesis balance between α- and β-globin chains of hemoglobin. There were many classics methods to diagnose thalassemia, but all of them had limitations. Although variations in the human β-globin gene cluster were mainly point mutations, novel large deletions had been described in recent years along with the development of DNA sequencing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…According to the phenotype of the proband and that of those two deletional β-thalassemia carriers, the deletion may cause β 0 thalassemia. Interestingly, the result of MLPA for the novel 7.2 kb deletion was the same as the one we had described ( Zhong et al, 2022 ). It has been shown that SMRT sequencing played an important role in thalassemia breakpoint detection.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…According to the phenotype of the proband and that of those two deletional β-thalassemia carriers, the deletion may cause β 0 thalassemia. Interestingly, the result of MLPA for the novel 7.2 kb deletion was the same as the one we had described ( Zhong et al, 2022 ). It has been shown that SMRT sequencing played an important role in thalassemia breakpoint detection.…”
Section: Discussionsupporting
confidence: 77%
“…There were AT-rich stretches around the 3′breakpoint, which may be significant in the recombination. A similar situation was observed in Taiwanese β-thalassemia and the case with a novel 7.2 kb deletion (Chr11:5222800-5230034, hg38) located in the HBB gene ( Zhong et al, 2022 ). According to the phenotype of the proband and that of those two deletional β-thalassemia carriers, the deletion may cause β 0 thalassemia.…”
Section: Discussionsupporting
confidence: 72%
“…This is due to the significant advantage of TGS in read length, which is much longer than that of NGS, making it easier to detect deletion variants in thalassemia genes ( 23 ). Medical practitioners have started to recognize TGS as the preferred method over NGS for detecting long deletion variants in the thalassemia gene ( Table 1 ) ( 23 , 27 , 28 , 30 , 31 , 33 ). On the other hand, NGS faces difficulties in accurately sequencing regions with abnormal GC content and highly repetitive sequences, which can lead to missed mutations and false-negative results.…”
Section: Advantages Of Tgs In Screening and Diagnosis Of Thalassemiamentioning
confidence: 99%